2005
DOI: 10.1289/ehp.7533
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution–Associated Changes in Lung Function among Asthmatic Children in Detroit

Abstract: In a longitudinal cohort study of primary-school-age children with asthma in Detroit, Michigan, we examined relationships between lung function and ambient levels of particulate matter ≤ 10 µm and ≤ 2.5 µm in diameter (PM 10 and PM 2.5 ) and ozone at varying lag intervals using generalized estimating equations. Models considered effect modification by maintenance corticosteroid (CS) use and by the presence of an upper respiratory infection (URI) as recorded in a daily diary among 86 children who participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 37 publications
(49 reference statements)
6
91
0
Order By: Relevance
“…This is similar to what is seen in human populations after environmental exposure to ozone (4,5). In contrast to our original hypothesis, IL-1b had no effect on ozone-induced airway hyperreactivity 1 day after ozone exposure.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is similar to what is seen in human populations after environmental exposure to ozone (4,5). In contrast to our original hypothesis, IL-1b had no effect on ozone-induced airway hyperreactivity 1 day after ozone exposure.…”
Section: Discussionsupporting
confidence: 85%
“…Hospitalizations for both asthma and for cardiovascular complaints increase immediately after environmental ozone exposure, followed by a second increase in hospitalizations after a 3-day lag (4,5). In guinea pigs, ozone exposure also has an acute and lag phase, which we have shown are associated with changes in eosinophil populations in lungs (3).…”
mentioning
confidence: 61%
“…Increases in ambient ozone concentration are associated with hospital admissions and reported symptoms from individuals with asthma and allergic rhinitis [1][2][3]. In challenge studies of asthmatic subjects, our research group has shown ozone induces eosinophilic infiltration in both upper and lower airways, decrements in pulmonary function, and enhances response to allergen [4][5][6].…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies regarding the relationship between air pollution and health effects have shown short-term changes in respiratory symptoms or respiratory health indicators in two susceptible groups: children and patients with respiratory disease. [1][2][3][4] These reports provide evidence of the sensitive and subtle adverse health effects of low-level exposure to air pollution.…”
Section: Introductionmentioning
confidence: 91%
“…1,2 Decreases in lung function related to PM 10 exposure have been reported. 3,4 Lung function measurement is a specific objective method of monitoring respiratory health and may detect subtle respiratory effects of air pollution. Indeed, measurements of pulmonary function may be a more sensitive way to evaluate the effect of air pollution on the lung health than relying on the appearance of respiratory symptoms or disease.…”
Section: Introductionmentioning
confidence: 99%